COUNSELING ON NUTRITION EDUCATION THROUGH VIDEO MEDIA AND LEAFLETS ON CHANGES IN KNOWLEDGE OF FRUIT AND VEGETABLE CONSUMPTION IN PUBLIC HEALTH STUDENTS: COUNSELING ON NUTRITION EDUCATION THROUGH VIDEO MEDIA AND LEAFLETS ON CHANGES IN KNOWLEDGE OF FRUIT AND VEGETABLE CONSUMPTION IN PUBLIC HEALTH STUDENTS - Panjaitan, Delita Br; Widyaningsih, Fadlilah; Parinduri, Anggi Isnani; Rifai, Achmad; Wasliati, Balqis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Fruits and vegetables are important components that the body needs to get nutritional content, where fruits and vegetables contain lots of vitamins, fiber, complex vegetable and animal proteins which are very useful for our bodies. The benefits of consuming fruits and vegetables apart from maintaining health conditions also prevent various chronic diseases that can be harmful to humans such as heart disease, cancer, obesity and other diseases. Adolescents are the most vulnerable age group in terms of consumption of vegetables and fruit, this habit will have a negative impact on health in the future. University students are a transitional group from adolescence to early adulthood. This research was conducted to look at the behavior of eating fruits and vegetables in college students. The study used cross sectional with a quantitative approach with a total of 64 peopleThe five senses that transmit knowledge to the brain are the eyes. This study aimed to determine the effect of nutrition education through video and leaflets media on fruit and vegetable consumption of changes. This study is one group pre-test post-test with the type of research pre experiment. Respondents are students of Colleges, the number of respondents as many as 64 respondents. Data were collected by questionnaire pre-test and post-test as well as the Food Frequency Questionnaire, and analyzed by Paired Samples T-test and Independent Sample T-test with alternative by Wilcoxon and Mann Whitney.